2022 IEEE Conference on Virtual Reality and 3D User Interfaces (VR) 2022
DOI: 10.1109/vr51125.2022.00048
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Observations: Using Virtual Reality to Augment Lab-Based Shoulder Surfing Research

Abstract: Figure 1: We explore the use of virtual reality (VR) for shoulder surfing research in the authentication research domain. We compare the impact of non-immersive/immersive VR observations on participants' observation performance and behaviour while shoulder surfing authentications. We demonstrate the strengths of VR-based shoulder surfing research by exploring three different authentication scenarios: (➊) automated teller machine (ATM), (➋) smartphone PIN, and (➌) smartphone pattern authentication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Researchers can scale up their sample sizes, recruit user study subjects from different countries, and adjust their systems without being required to purchase or build special hardware. However, despite prior works that validated VR's use for empirical real-world research [27,29,31,56], it is important to 1) acknowledge potential technical limitations and 2) have a clear vision of what can be expected from evaluations that are conducted on virtual artefacts. For example, investigating Tap 's usability in the lab using better hand tracking technology (e.g., an OptiTrack system [39]) may impact participants' usability perception.…”
Section: Rvr 3 : a Complementary Research Methodsmentioning
confidence: 99%
“…Researchers can scale up their sample sizes, recruit user study subjects from different countries, and adjust their systems without being required to purchase or build special hardware. However, despite prior works that validated VR's use for empirical real-world research [27,29,31,56], it is important to 1) acknowledge potential technical limitations and 2) have a clear vision of what can be expected from evaluations that are conducted on virtual artefacts. For example, investigating Tap 's usability in the lab using better hand tracking technology (e.g., an OptiTrack system [39]) may impact participants' usability perception.…”
Section: Rvr 3 : a Complementary Research Methodsmentioning
confidence: 99%
“…We suggest such critical moments be incorporated into evaluation scenarios (e.g. through insitu evaluations, acted out bystander interactions, nested simulated realities [26][27][28]), or be assessed after-the-fact (e.g. think aloud approaches where participants reflect on the suitability of the proposed approach versus standardised baselines across these critical moments -replicating our Assessing Awareness Needs evaluation design).…”
Section: The Need For New Approaches To Vr User-bystander Interaction...mentioning
confidence: 99%
“…Others argued that VR combines the internal validity of controlled lab studies with the external validity of field studies [17,36,40]. There is a plethora of additional works that commented on using VR as a research platform (e.g., [3,38,40,42,61,63]).…”
Section: Virtual Reality As a Research Platformmentioning
confidence: 99%
“…We implemented a VR prototype of FeetAuth in Unity 3D (C#). Previous work by Mäkelä et al [36] and Mathis et al [38][39][40] showed that using VR as a research method to conduct user studies on public displays and to evaluate real-world prototype authentication systems is feasible. A VR-powered research approach also enabled us to conduct research in a relatively realistic environment, which is challenging to replicate in a physical lab.…”
Section: Implementation and Apparatusmentioning
confidence: 99%